Acute urinary retention as first sign of myelin oligodendrocyte glycoprotein antibody disease (MOGAD) - Case report and literature review - Mariana Dias Capinha; Andreia Cardoso; Catarina Tinoco; Ana Sofia Araújo; Luís Pinto; Aparício Coutinho; Emanuel Dias; Miguel Mendes (Urology Case Reports)
Myelin oligodendrocyte glycoprotein antibody disease is a rare, demyelinating condition of the central nervous system. We report a case of a male presenting with acute urinary retention and brainstem lesion, highlighting an atypical initial manifestation of the disease. Serum testing confirmed anti-myelin oligodendrocyte glycoprotein antibodies. The lesion resolved without corticosteroid therapy. The patient later initiated Rituximab to prevent relapse, demonstrating favorable clinical progress. This case underscores the importance of considering neuro-urological causes in atypical presentations, and the necessity of interdisciplinary approaches between Neurology and Urology. Further research is essential to clarify protocols, particularly in less common clinical presentations.